The Influence of Students Motivation and Learning Readiness on Students Learning Outcomes in IPS Subjects Grade IX SMP Negeri 2 Siantar - Koko Okto Rizki Sianipar; Injen Pardamean Butar-Butar; Sotarduga Sihombing (MultiTech Publisher, 2023)
This research aims to determine the influence of Learning Motivation and Readiness to learn on student learning outcomes in social studies subjects in class IX SMP NEGERI 2 SIANTAR. The variables in this research are learning motivation and readiness to learn as independent variables and learning outcomes as the dependent variable. This type of research is quantitative research with a quantitative descriptive approach, with a research population of class IX students at SMP NEGERI 2 SIANTAR and a research sample of class IX students at SMP NEGERI 2 SIANTAR consisting of 155 students selected using Simple Random Sampling . Data collection techniques use instruments: (1) Learning Motivation questionnaire, (2) Learning Readiness questionnaire, and (3) Learning Outcomes questionnaire. The results of this research show that: (1) there is a positive and significant influence of learning motivation on learning outcomes, this result can be seen in the t test where the calculated t value of Learning Motivation (2.051) > t table value (1.65474) which means that this variable significant. (2) there is a positive and significant influence of learning readiness on learning outcomes (1.903) > t table value (1.65474) which means this variable is significant. (3) Learning Motivation and Learning Readiness together influence learning outcomes, these results can be seen in the F test where the calculated F value (14.348) is > compared to the F table value (2.66). The R Square coefficient of determination test was found to be 0.159, meaning that 15.9% of the Learning Motivation and Learning Readiness variables had an influence on student learning outcomes at the SIANTAR NEGERI 2 SMP school and the remaining 84.1% was the influence of other variables not examined in this research.